Mathematics Learning Innovation During the Covid-19 Pandemic in Indonesia: a Systematic Literature Review - Indah Suciati; Dewi Sri Wahyuni; Nurhalida Sartika (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this study is to analyze mathematics learning innovations during the Covid-19 pandemic in Indonesia. The research method used is Systematic Literature Review. Data collection was carried out by documenting and reviewing articles related to learning mathematics during the Covid-19 pandemic which were published in the 2020-2021 period in national journals. The data analysis technique used refers to the interactive model by Miles & Huberman which consists of 4 stages, namely data collection, data reduction, data presentation, and drawing conclusions. These findings indicate that (1) Mathematics learning innovation during the Covid-19 pandemic in Indonesia can be done online, offline, or blended learning. The implementation is by means of E-learning, the use of software, the use of learning media, or the use of innovative, effective, and creative models, approaches, and learning methods such as blended learning which are considered in accordance with the conditions and obstacles faced by educators and students, (2) Mathematics learning assessments can be carried out using online, manual, or blended learning-based assessments, (3) The obstacles faced during the Covid-19 pandemic are in the form of unsupported learning facilities and infrastructure, teacher competence and readiness that is not possible, psychological and low ability of students, assessment of learning outcomes that do not go well and is not comprehensive in all areas, lack of cooperation and family awareness, and abstract mathematical objects.